Effectiveness of Physical Exercise Program on Reducing Blood Pressure in Hypertension Patients - Kina Hutajulu; Bayhakki Bayhakki; Reni Zulfitri (Indonesian Journal of Global Health Research, 2024)
Hypertension is a chronic disease, called the silent killer. WHO data shows that the number of people with hypertension continues to increase. In Riau Province, the prevalence of hypertension increased from 20.9% (2013) to 29.1% (2018). Hypertension will cause various complications such as encephalopathy, heart disease, hemorrhagic stroke, kidney failure, heart failure, and others. Action needs to be taken to reduce the increasing number of hypertension cases. Objective: This study examines the effectiveness of a physical exercise program in reducing blood pressure in hypertension patients at the Pangkalan Kuras II Health Center. Method: It used a pre-test and post-test experimental design involving 101 hypertensive patients, primarily aged 46-64 years (85.1%) and mostly female (86.14%). The program included walking three times a week and exercising twice a week for three weeks. Blood pressure was measured using a manual device. The majority of participants had grade II hypertension. Result: The Wilcoxon Signed Rank Test showed significant reductions in both systolic (4.72 mmHg) and diastolic (3.13 mmHg) blood pressure, with a p-value of 0.000. Conclusions: This numbers indicates that regular physical exercise, such as walking and exercise, effectively lowers blood pressure in hypertensive patients.